Quality of Work Life among Midwives Working in Zanjan University of Medical Sciences Hospitals - maryam sakkaki; khadijeh hajimiri; fariba farsi (Zanjan University of Medical Sciences and Health Services, 2013)
Background and Objectives: Among modern organizations with their competitive nature, only the organizations can continue working that improve their performances. Hospitals as modern organizations should pay more attention on quality of work life of their staff. The aim of this study was to assess the quality of work life among midwives working in hospitals of Zanjan University of Medical Sciences in 2012. Material and Methods: In this descriptive cross-sectional study, all midwives (n=85) working in the hospitals of Zanjan University of Medical Sciences were recruited to the study. Data were gathered using: 1) demographic characteristics questionnaire and 2) a 30-item five-point Likert scale based on the Walton Life Quality questionnaire. Results: The results showed that 38.8% of the midwives had low quality of work life and 61.2% had medium quality of work life. None of the participants reported high quality of work life. There were no significant relationships between the quality of work life with age, marital status, shift work, type of working contract, work precedent and setting (P<0.05). Conclusion: The quality of work life of midwives working in the hospitals of Zanjan University of Medical Sciences was not appropriate and they were not satisfied with their work. Lack of job satisfaction can affect the quality of services provided by them. The results of this study should be noticed by managers to identify midwiveschr('39') needs and enhance their quality of work life.